2006
DOI: 10.1111/j.1365-2966.2006.10856.x
|View full text |Cite
|
Sign up to set email alerts
|

The temperature and ionization structure of the emitting gas in H II galaxies: implications for the accuracy of abundance determinations

Abstract: We propose a methodology to perform a self‐consistent analysis of the physical properties of the emitting gas of H ii galaxies adequate to the data that can be obtained with the 21st century technology. This methodology requires the production and calibration of empirical relations between the different line temperatures that should supersede currently used ones based on very simple, and poorly tested, photoionization model sequences. As a first step to reach these goals, we have obtained simultaneous blue to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
128
0
8

Year Published

2009
2009
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(146 citation statements)
references
References 93 publications
10
128
0
8
Order By: Relevance
“…found by Hägele et al (2006) for HII galaxies. The values of the derived electron temperatures for these two knots are listed in Table 5.…”
Section: Physical Conditions Of the Gasmentioning
confidence: 88%
See 1 more Smart Citation
“…found by Hägele et al (2006) for HII galaxies. The values of the derived electron temperatures for these two knots are listed in Table 5.…”
Section: Physical Conditions Of the Gasmentioning
confidence: 88%
“…The atomic coefficients used here are the same as in Hägele et al (2006). We took as sources of error the uncertainties associated with the measurement of the emission-line fluxes and the reddening correction and we propagated them through our Table 4.…”
Section: Physical Conditions Of the Gasmentioning
confidence: 99%
“…In the study of galaxies with WR signatures from the Sloan Digital Sky Survey (SDSS) carried out by Brinchmann et al (2008), it is also found that WR galaxies show an elevated N/O relative to non-WR galaxies. Additionally, an N/O excess is reported in other six BCDs with log(N/O) > −1.3 and a prominent WR blue bump in their optical integrated spectra (Hägele et al 2006(Hägele et al , 2008Pérez-Montero et al 2010). On the other hand, the high N/O found in metalpoor halo stars indicates that another mechanism polluting the ISM with N, other than WR star winds, might exist.…”
Section: Introductionmentioning
confidence: 97%
“…To calculate the electron temperature t([Oiii]), we use the expressions from Hägele et al (2006Hägele et al ( , 2008 that are based on the TEMDEN task under the IRAF nebular package. The distribution functions and the maps of this temperature in the three observed galaxies are shown in Fig.…”
Section: Electron Temperature and Densitymentioning
confidence: 99%
See 1 more Smart Citation